CORRUPTION AND ITS IMPACT ON SUSTAINABLE DEVELOPMENT IN NIGERIA - AKE MODUPE (International Studies Journal)
Corruption in Nigeria is a severe hindrance to the country's long-term prosperity. This study examines the many impacts of corruption on Nigeria's sustainable development trajectory. It is based on a comprehensive examination of existing literature, including insights from many scholarly sources. The study begins by defining corruption and sustainable development in Nigeria, delving into their historical contexts and philosophical frameworks. It investigates corruption's evolution and its complex relationships with political, economic, and social factors. Various forms of corruption are investigated in the political, corporate, judicial, and law enforcement sectors, with institutional inadequacies, rent-seeking behaviour, and cultural issues identified as major drivers. Furthermore, the analysis examines the impact of corruption on the Sustainable Development Goals (SDGs), focusing on economic consequences such as misappropriation of public funds and decreased foreign investment, as well as social and political consequences such as eroded trust in governmental institutions and societal unrest. The study also assesses existing anti-corruption efforts in Nigeria using case studies and empirical facts, building on lessons from similar situations. Finally, it identifies research gaps, examines future directions, and makes policy recommendations for combating corruption and promoting sustainable development in Nigeria.